LA PARTECIPAZIONE CHE FA BENE ALL’AMBIENTE: OLTRE AARHUS E A FAVORE DELLO SVILUPPO DI UNA SCIENZA CIVICA E DI COMUNITÀ - Fornabaio, Lara; Poto, Margherita (REVISTA DIREITO DAS POLÍTICAS PÚBLICAS)
The Italian administrative court (first instance : Tribunale Amministrativo Regionale per il Lazio (Sezione I Ter) 5 maggio 2016, n. 5274.) quenches a decision of the Regione Lazio that approved the extension to certain categories of waste without a sufficient scrutiny on the effective environmental risks and without involving the interested parties in the decision making process. According to the court, the procedural guarantees are the paradigm for the explication of the precautionary principle and shall be implemented, regardless of whether the Aarhus Convention applies or not. The participatory rights shall be granted to the interested parties, including agricultural holdings.